B2B Solution using WebSphere business integration V4.1 and WebSphere business connection V1.1 - Gavin, Lee (IBM redbooks., 2003)
The world of e-commerce is changing rapidly. Some ten years ago, e-commerce was mostly defined as participating in an Electronic Data Interchange (EDI) initiative. Today, e-commerce means much more than just EDI: it means supporting interactive Web sites; it means enabling the communications with multiple exchanges; it means using XML and the Internet to conduct interactive business-to-customer and business-to-business communications. This IBM Redbooks publication explores some of the possibilities using products from WebSphere Business Integration V4.1 and WebSphere Business Connect V1.1 product suites. For more up-to-date information about WebSphere B2B, please refer to the following books: B2B solutions using WebSphere Partner Gateway V6.0, http://www.redbooks.ibm.com/abstracts/sg247109.html?Open and Secure Production Deployment of WebSphere Business Integration Connect, http://www.redbooks.ibm.com/abstracts/sg246457.html?Open. Please note that the additional material referenced in the text is not available from IBM.